An Experiment on Nonsampling Errors - Sauls, Eugene H. (Journal of Accounting Research, 1970)
That hereafter, whenever practicable and reasonable, and where the aggregate amount of notes and accounts receivable represents a significant portion of the current assets or of the total assets of a concern, confirmation of notes and accounts receivable by direct communication with the debtors shall be regarded as generally accepted auditing procedure in the examination of the accounts of a concern whose financial statements are accompanied by an independent certified public accountant's report, and that the method, extent, and time of confirming receivables or a part thereof, be determined by the independent certified public accountant as in other phases of procedure requiring the exercise of his judgmentl